Efecto genético del aislamiento geográfico de la liebre negra (Lepus insularis), endémica de Isla Espíritu Santo, Baja California Sur, México - Cervantes, Fernando; Castañeda, Mario (THERYA, 2012)
This research assessed the degree of genetic divergence between Lepus insularis and L. californicus xanti from the Baja California Peninsula as a consequence of the geographical isolation of the former using allozymic analyses. Results were compared and contrasted with the similar biogeographical condition for the taxon pair L. c. sheldoni, from Carmen Island, and L. c. martirensis, from the northern range of the Peninsula. Heart and kidney tissues were used to obtain 26 loci by the conventional protein electrophoresis technique with starch gels. Estimations of genetic variability with the software BIOSYS showed that L. c. xanti was the most variable population while in contrast L. insularis was poorly variable. Research data confirmed a clear genetic divergence between L. insularis and L. c. xanti supporting the notion that geographical isolation in Baja California islands may slow or limit gene flow contributing to losses of genetic variation that leads to genetic differentiation.